Kondisi Mental Para Pengahafal Al-Qur’an di Masa Pandemi - Alisa Qothrunnada Munawaroh; Muhtarom Muhtarom; Tri Indah Hapsari; Waliko Waliko (MAGHZA, 2021)
The Covid-19 pandemic affects the emotional mental condition of the tahfidz al-Qur'an Islamic boarding school students. The existence of Covid-19 has had a physical and psychological impact on every student. The students who are in the boarding school environment must practice social distancing. The students at the Islamic boarding school must stay in the cottage with the application of the quarantine method. This study aims to obtain and provide an overview of the mental and emotional disorders of students in Islamic boarding schools who are currently in quarantine. This type of research is qualitative research with this research method being descriptive analysis. The data collection techniques in this study, namely observation, interviews, and documentation. Based on data analysis, tahfidz students from Islamic boarding schools in Banyumas experienced a decrease in reduced deposits and some even could only do muraja'ah.